Nyctobadistes gen. nov. (Isopoda: Asellota: Munnopsidae), a new genus from Tasmanian waters, Australia, with the description of a new species - Merrin, Kelly L. (Zootaxa, 2011)
A new genus and new species of Munnopsidae Lilljeborg, 1864 is described. Nyctobadistes gen. nov. is represented by a single species, Nyctobadistes hamatus sp. nov. and was collected from off Tasmania, south-eastern Australia. Nyctobadistes gen. nov. is similar to Bathybadistes Hessler and Thistle, 1975, however, it can be distinguished from this genus by the combination of: the lack of apical setae on the dorsal body spines; the lack of lateral extensions on the natasomal pereonites; the slender carpus of at least pereopod 6; and the anterolateral margins of the pleon lack a spine and apical seta.